Mass Spectrometry in Russia. Issue 6 (December 2013) - Zaikin, Vladimir G.; Sysoev, Alexander A.
The present review covers the main research in the area of mass spectrometry from the 1990s which was about the same time as the Russian Federation emerged from the collapse of the Soviet Union (USSR). It consists of two main parts—application of mass spectrometry to chemistry and related fields and creation and development of mass spectrometric technique. Both traditional and comparatively new mass spectrometric methods were used to solve various problems in organic chemistry (reactivity of gas-phase ions, structure elucidation and problems of identification, quantitative and trace analysis, differentiation of stereoisomers, derivatization approaches etc.), biochemistry (proteomics and peptidomics, lipidomics), medical chemistry (mainly the search of biomarkers, pharmacology, doping control), environmental, petrochemistry, polymer chemistry, inorganic and physical chemistry, determination of natural isotope ratio etc. Although a lot of talented mass spectrometrists left Russia and moved abroad after the collapse of the Soviet Union, the vitality of the mass spectral community proved to be rather high, which allowed the continuation of new developments in the field of mass spectrometric instrumentation. They are devoted to improvements in traditional magnetic sector mass spectrometers and the development of new ion source types, to analysis and modification of quadrupole, time-of-flight (ToF) and ion cyclotron resonance (ICR) analyzers. The most important achievements are due to the creation of multi-reflecting ToF mass analyzers. Special attention was paid to the construction of compact mass spectrometers, particularly for space exploration, of combined instruments, such as ion mobility spectrometer/mass spectrometer and accelerating mass spectrometers. The comparatively young Russian Mass Spectrometry Society is working hard to consolidate the mass spectrometrists from Russia and foreign countries, to train young professionals on new appliances and regularly holds conferences on mass spectrometry. For ten years, a special journal Mass-spektrometria has published papers on all disciplines of mass spectrometry.